The Perception of Quality: Mapping Product and Service Quality to Consumer Perceptions - Kenyon, George N (Springer, 2015)
Exploring the concept of quality management from a new point of view, this book presents a holistic model of how consumers judge the quality of products. It links consumer perceptions of quality to the design and delivery of the final product, and presents models and methods for improving the quality of these products and services. It offers readers an improved understanding of how and why the design process must consider how the consumer will perceive a product or service. In order to facilitate the presentation and understanding of these concepts, illustrations and case examples are also provided throughout the book.